Od deviantů k rodičům: Neheterosexuální maskulinity v současných českých televizních seriálech - Zdeněk Sloboda (Gender a Výzkum, 2015)
Since about 2004, the boom in the production of original Czech television series has been accompanied by the slow but steady increase in the appearance of non-heterosexual characters on TV. This analysis focuses on gay characters: what they are like, why and how they appear and disappear, how their non-heterosexuality is established and how it develops in the narrative of the series. A notable change can be observed in how gay male characters are being depicted: from depictions of mostly miserable characters whose coming out is their only dramatic potential in the narrative, to more complex portraits of characters who are incorporated into the story, experiencing love, partnerships and even parenthood – elements otherwise normal in series narratives. Alongside this more descriptive type of analysis, the author draws on Connell and Messerschmidt’s concept of hegemonic masculinity to draw attention to representations of practices that produce the masculinity of non-heterosexual (male) characters as subordinate , as complicit, and, in the case of recent characters, even as hegemonic. The representation of non-heterosexual characters as hegemonically masculine seems to be a form of ‘narrative redemption’ through homonormativity.